Morphological Teaching Strategies to Enhance Students’ Vocabulary Knowledge and Reading Comprehension - Sulistyawati, Elizabeth; Nugroho, Alvian; Bram, Barli (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2021)
A number of studies have shown that morphological awareness contributes to the improvement of the comprehension of student reading and vocabulary learning, interest in the importance of language acquisition and instruction of morphological awareness is increasing. This research emphasizes the use of morphological techniques used in reading comprehension to enhance the vocabulary awareness of prefixes and suffixes of students and to contribute to the development of vocabulary acquisition. This literature review was conducted to incorporate research results to assess whether such training led to increased understanding of reading and development of vocabulary. First, researchers need to collect relevant information related to morphological and teaching strategies in the teaching and learning process of English. Second, researchers can analyze data regarding the advantages and disadvantages of morphological strategies and instructions in the English teaching and learning process. Third, researchers identified the important role of morphological awareness that has been applied by students and the need to implement morphological strategies to help second language learners to acquire English language skills. Finally, learners can conclude some important things related to the application of morphology learning strategies to engage the teaching and learning process so that learners can achieve learning objectives regularly.